Development and validation of an instrument for monitoring child development indicators - Sonia I. Venancio; Maritsa C. Bortoli; Paulo G. Frias; Elsa R.J. Giugliani; Cláudia R.L. Alves; Miriam O. Santos (Brazilian Society of Pediatrics, 2020)
Objective: To create and validate an instrument for child development monitoring. Methods: Methodological study, based on the World Bank's proposition to monitor child development indicators in low‐ and middle‐income countries. The stages of the study included the following: development of an inventory of items for child development evaluation, based on open access instruments; content validation by a group of experts on the topic, using consensus techniques; selection of questions to describe children and their families; pre‐test of the instrument during the vaccination campaign in 2016 in three municipalities, and conducting cognitive interviews. Results: A total of 431 items were sent for the evaluation of the specialists; 77 were initially excluded and the others were evaluated in‐person by the group, with 162 items covering the motor, cognitive, language, and socio‐emotional domains, distributed in ten age ranges. Questions about health, nutrition, early learning, protection and safety, and responsive care were also included. The instrument was applied by volunteer undergraduate students to 367 mothers of children under 5 years, showing good adherence of the caregivers. The time of application of the questionnaire was, on average, 20 minutes. The cognitive interviews allowed the final adjustment of 19 items of the instrument for better understanding by the caregivers. Conclusions: The instrument created and validated by experts fills a gap, as it allows a comprehensive evaluation of the development of children under 5 years at the population level, using a fast and inexpensive tool, and can be useful for monitoring indicators of development in Brazilian children in vaccination campaigns. Resumo: Objetivo: Elaborar e validar um instrumento para o monitoramento de indicadores do desenvolvimento infantil. Métodos: Estudo metodológico baseado na proposta do Banco Mundial para medir indicadores do desenvolvimento infantil em países de baixa e média renda. As etapas do estudo contemplaram: elaboração de um inventário de itens para avaliação do desenvolvimento infantil, com base em instrumentos de livre acesso; validação de conteúdo por um grupo de especialistas no tema, com técnicas de consenso; seleção de questões para descrever as crianças e suas famílias; pré‐teste do instrumento durante a campanha de vacinação de 2016 em três municípios e realização de entrevistas cognitivas. Resultados: Foram enviados 431 itens para avaliação dos especialistas, 77 foram excluídos e os demais apreciados presencialmente pelo grupo. No fim foram selecionados 162 itens que abrangeram os domínios motor, cognitivo, de linguagem e socioemocional, distribuídos em 10 faixas etárias. Foram incluídas questões sobre saúde, nutrição, aprendizagem precoce, proteção e segurança e cuidado responsivo. O instrumento foi aplicado por universitários voluntários a 367 mães de crianças menores de cinco anos, mostrou boa adesão dos cuidadores. O tempo médio de aplicação do questionário foi 20 minutos. As entrevistas cognitivas permitiram ajustar 19 itens do instrumento para melhor compreensão dos cuidadores. Conclusões: O instrumento construído e validado por especialistas preenche uma lacuna, que permite uma avaliação abrangente do desenvolvimento de crianças menores de cinco anos, em nível populacional, de forma rápida e barata, pode ser útil para o monitoramento de indicadores do desenvolvimento em campanhas de vacinação.